2022
DOI: 10.1038/s41598-022-09533-x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental pyrethroid exposure and age influence phenotypes in a Chd8 haploinsufficient autism mouse model

Abstract: Hundreds of genes have been associated with autism spectrum disorder (ASD), including loss-of-function mutations in chromodomain helicase DNA binding protein 8 (Chd8). Environmental factors also are implicated in autism risk and have the potential to exacerbate phenotypes in genetically sensitized backgrounds. Here we investigate transcriptional and behavioral phenotypes in a Chd8 haploinsufficient (Chd8V986*/+) mouse line exposed to the pesticide deltamethrin (DM) from conception to postnatal day 22. Vehicle-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Previous studies on Chd8 -mutant mice and human neurons suggested multiple mechanisms that may underlie CHD8-related brain deficits ( Sugathan et al, 2014 ; Cotney et al, 2015 ; Wang et al, 2015 ; Breuss and Gleeson, 2016 ; Durak et al, 2016 ; Katayama et al, 2016 ; Gompers et al, 2017 ; Platt et al, 2017 ; Wang et al, 2017 ; Andreae and Basson, 2018 ; Jung et al, 2018 ; Suetterlin et al, 2018 ; Wade et al, 2018 ; Xu et al, 2018 ; Zhao et al, 2018 ; Hulbert et al, 2020 ; Jimenez et al, 2020 ; Sood et al, 2020 ; Cherepanov et al, 2021 ; Ding et al, 2021 ; Ellingford et al, 2021 ; Hurley et al, 2021 ; Kawamura et al, 2021 ; Kweon et al, 2021 ; Weissberg and Elliott, 2021 ; Chen et al, 2022 ; Coakley-Youngs et al, 2022 ; Dong et al, 2022 ; Haddad Derafshi et al, 2022 ; Jimenez et al, 2022 ; Kerschbamer et al, 2022 ; Lee et al, 2022 ; Paulsen et al, 2022 ; Thudium et al, 2022 ; Tu et al, 2022 ; Villa et al, 2022 ; Yu et al, 2022 ; Hayot et al, 2023 ). However, mechanisms underlying the male–female differences in CHD8-related ASD are poorly understood ( Jung et al, 2018 ; Cherepanov et al, 2021 ; Yu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on Chd8 -mutant mice and human neurons suggested multiple mechanisms that may underlie CHD8-related brain deficits ( Sugathan et al, 2014 ; Cotney et al, 2015 ; Wang et al, 2015 ; Breuss and Gleeson, 2016 ; Durak et al, 2016 ; Katayama et al, 2016 ; Gompers et al, 2017 ; Platt et al, 2017 ; Wang et al, 2017 ; Andreae and Basson, 2018 ; Jung et al, 2018 ; Suetterlin et al, 2018 ; Wade et al, 2018 ; Xu et al, 2018 ; Zhao et al, 2018 ; Hulbert et al, 2020 ; Jimenez et al, 2020 ; Sood et al, 2020 ; Cherepanov et al, 2021 ; Ding et al, 2021 ; Ellingford et al, 2021 ; Hurley et al, 2021 ; Kawamura et al, 2021 ; Kweon et al, 2021 ; Weissberg and Elliott, 2021 ; Chen et al, 2022 ; Coakley-Youngs et al, 2022 ; Dong et al, 2022 ; Haddad Derafshi et al, 2022 ; Jimenez et al, 2022 ; Kerschbamer et al, 2022 ; Lee et al, 2022 ; Paulsen et al, 2022 ; Thudium et al, 2022 ; Tu et al, 2022 ; Villa et al, 2022 ; Yu et al, 2022 ; Hayot et al, 2023 ). However, mechanisms underlying the male–female differences in CHD8-related ASD are poorly understood ( Jung et al, 2018 ; Cherepanov et al, 2021 ; Yu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of zebrafish embryos to 6PPD (0.22 mg/L; 2–120 h postfertilization) caused developmental toxicity and altered hormone levels and gene expressions in embryos . Although developmental effects have not been observed in mammals for 6PPD and 6PPDQ, these results suggest that the mammalian embryonic stage may also be sensitive to these chemicals due to the physiologic similarities to the model organisms. , In mammalian systems, the placenta serves as a barrier to protect the fetus from circulating environmental contaminants. , However, some contaminants with specific physicochemical properties or binding activities can cross the placental barrier, leading to fetal exposure. It is currently unclear whether 6PPD and 6PPDQ can be transferred from exposed mothers to their embryos in mammalian systems. Moreover, the impact of 6PPD and 6PPDQ on nuclear receptor pathways, such as thyroid hormone receptors (TRs), retinoic acid receptor (RAR), and retinoid X receptor (RXR) that are essential for embryonic development, remains unknown.…”
Section: Introductionmentioning
confidence: 97%
“…Current understanding supports that most cases of NDDs arise from complex interactions between candidate genes and/or environmental factors ( Kim and Leventhal, 2015 ; Vorstman et al, 2017 ; Hollander et al, 2020 ). In line with this premise, mouse models with mutations in a single high-confidence gene are sometimes found to have absent or mild phenotypes related to clinical profiles, raising the possibility that an additional environmental challenge or “hit,” such as PNS, is necessary to drive the emergence of abnormal behaviors ( Jiménez et al, 2022 ; Lord et al, 2022 ). In this paper, we review the literature examining PNS in genetic mouse models of NDDs, and discuss potential experimental factors that could influence results of these studies.…”
Section: Introductionmentioning
confidence: 99%